Perbandingan Kinerja Berahi dan Level Estradiol Kambing Kacang dan Kambing Nubian yang Diinduksi dengan PGF2α - Mulyadi Adam; Raja Nurul Huda; Widya Zahara; Tongku Niswan Siregar; Sri Wahyuni; Cut Nila Thasmi; Rosmaidar Rosmaidar (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
The experiment was conducted to compare estrous performance between and estradiol level kacang and Nubian goats estrous induction by prostaglandin F2 alpha (PGF2α). Eight female goats were divided into two groups, groups 1 (K1) consisted five Nubian goats and group 2 (K2) included three kacang goats with criterias as follows: age 1.5-3.0 years old, not pregnant, at least two months postpartum, and healthy clinically. All goats were estrous synchronized by double injection 7,5 mg PGF2α intramuscularly with 10 days interval. Goats that appeared estrus symptoms were mated naturally to a male goat. Determination of estrous intensity was performed using scoring method. Blood samples were taken at the first time the goats were mated (day 0). The measurement of estradiol concentration was done by enzyme linked immunosorbent assay (ELISA) method. Data of intensity, onset, duration, and estradiol level were analyzed using t test. The results showed that the rate of intensity, onset, duration, and estradiol level of estrous at KI vs KII were 2.08±0.52 vs 1.85±0.67, 56.00±34.11 vs 40.80±18.20 hours, and 24.00±26.15 vs 33.80±9.10 hours, and 103.51±42.49 vs 67.95±38.44 pg/ml (P>0,05). It can be concluded there was no difference of estrous performance and estradiol level between kacang and Nubian which estrous induction with PGF2α. The relationship between the intensity of estrus estradiol level in the Nubian goats was 0.995 while the kacang goats was 0.890.